Mengukur Tingkat Pemahaman Pelatihan PowerPoint Menggunakan Quasi-Experiment One-Group Pretest-Posttest - William William; Hita Hita (Jurnal SIFO Mikroskil, 2019)
The use of technology in the world of education is an effort to improve the delivery of material to students. Mastery of PowerPoint as the popular tools in making teaching material is needed to be well understood by teachers in order to be able to arrange teaching materials in accordance with their respective fields. These training activities aim to increase understanding of teachers related to PowerPoint so that they are able to use it well. The descriptive statistical research method and the Quasi-Experiment One-Posttest research design were used to determine whether this activity was able to influence the teachers. The teachers were asked to do a pretest before being given treatment to then be given the posttest. The results of the tests showed an increase in teachers' understanding of PowerPoint as the increase in the average value from 74.67 to 76.13 as well as the increase in the percentage of those who got the A, B, and C values from 76% to 84%. Besides this, the even distribution of knowledge has also been increased by showing a decrease in the standard deviation value from 10.93 to 10.12. These can be concluded that this activity can improve teachers' understanding of PowerPoint.